2013
DOI: 10.3832/ifor0856-006
|View full text |Cite
|
Sign up to set email alerts
|

Sodium and potassium allocation under drought stress in Atlas mastic tree (Pistacia atlantica subsp. mutica)

Abstract: © iForest -Biogeosciences and Forestry IntroductionAmong the many physiological features by which plants cope with water shortage, maintaining cation uptake and mobility in different tissues plays many crucial roles to deal with water deficit. Monitoring of cation changes under soil water shortage is so important that it was recently used as a drought tolerance index for selecting cultivars (Achakzai 2007(Achakzai , 2008. Nutrients uptake and consequent cation translocation highly depend on transpiration strea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
0
5
0
2
Order By: Relevance
“…However, the RE of K remains considerable and could be expected to be higher in dry ecosystems, compensating for the low capacity for K uptake in dry conditions (in comparison with plants at wetter sites as reported in some studies; see, e.g. Fayyaz et al, 2013;Tomlinson et al, 2013). Moreover, the capacity of plants to retain K in arid environments could be improved by lower leaching (Singer, 1989).…”
Section: Box 1 Main Ecophysiological Roles Of Kmentioning
confidence: 96%
See 1 more Smart Citation
“…However, the RE of K remains considerable and could be expected to be higher in dry ecosystems, compensating for the low capacity for K uptake in dry conditions (in comparison with plants at wetter sites as reported in some studies; see, e.g. Fayyaz et al, 2013;Tomlinson et al, 2013). Moreover, the capacity of plants to retain K in arid environments could be improved by lower leaching (Singer, 1989).…”
Section: Box 1 Main Ecophysiological Roles Of Kmentioning
confidence: 96%
“…This effect is related to the role K plays in enhancing photosynthetic CO2 fixation, improving the transport of photosynthates into sink organs and inhibiting the transfer of photosynthetic electrons to O2, thereby reducing ROS production (Cakmak, 2005). Many field studies have thus observed correlations between K concentrations in plants and soils and mechanisms of drought avoidance (Nandwal et al, 1998;Arquero et al, 2006;Teixeira et al, 2008;Fayyaz et al, 2013;Tomlinson et al, 2013). Many physiological and metabolomic studies in garden and potted plants (Babita et al, 2010;Cuéllar et al, 2010) and in crops (Römheld & Kirkby, 2010;Waraich et al, 2011;Wang et al, 2013), and some studies across environmental gradients under field conditions (Kadar & Foldesi, 2001), have observed a strong link between K concentrations and the resistance and adaptation of plants to drought.…”
Section: Box 1 Main Ecophysiological Roles Of Kmentioning
confidence: 99%
“…Some studies have suggested that the K + content in roots and shoots is independent and shoot K + content is related to transpiration. In contrast, variations in root K + content are not related to leaf transpiration rate (Fayyaz et al, 2013). Therefore, plants with high K + can absorb more water under drought stress (El-Hadi et al, 1997).…”
Section: Figure 2 Effects Of Exogenous Peg On Plants Flesh and Dry (F...mentioning
confidence: 99%
“…Kalium berfungsi untuk menjaga tekanan osmotik serta keseimbangan cairan atau air di dalam sel. Sintesis dan akumulasi senyawa osmolit berperan dalam pengaturan tekanan osmotik sel serta melindungi sel-sel dengan cara mengikat spesies oksigen reaktif (ROS) (Fayyaz et al, 2013). Berdasarkan uraian diatas maka perlu dilakukan penelitian pengaruh suhu, pemupukan K dan N terhadap pertumbuhan tanaman padi.…”
Section: Pendahuluanunclassified